Review—Recent Advances in Electrochemical Impedance Spectroscopy Based Toxic Gas Sensors Using Semiconducting Metal Oxides. Issue 3 (28th February 2020) - Balasubramani, V.; Chandraleka, S.; Rao, T. Subba; Sasikumar, R.; Kuppusamy, M. R.; Sridhar, T. M.
Abstract : Electrochemical Impedance Spectroscopy (EIS) in the past few years has been used to design gas sensors. EIS based gas sensing has been considered as an ultra-sensitive technique to identify and measure different toxic gases. Their sensing performance has been superior when compared to other conventional techniques. Impedance makes it possible to investigate the finer changes occurring on the surface of sensing layers leading to the identification of the target gases such as H2 S. The measurements are carried out by scanning the electrode surface with a mixture of frequencies from 1 Hz to 10 MHz and recording the response as Nyquist and Bode plots. From these plots, the results can be used to elucidate the electrochemical phenomena. The acquired impedance data can be fitted into equivalent circuits and this is further modeled to obtain information about the interfacial phenomena like grain bulk resistance, grain boundary resistance, interface between electrode and sensing film resistance. These phenomena support the sensing of toxic gases from ppm - ppb level. This article focuses on impedance spectroscopy and its relevance to sensors, challenges in detecting toxic gases on the electrode surfaces prepared using semiconducting metal oxides, doped metal oxides and graphene based composites along with the research gaps, current innovations and future directions. EIS based gas sensors have high selectivity, sensitivity, reproducibility, long term stability and they also assist prediction of the electrochemical mechanisms for the analyte gases.